Creación de una microempresa comunitaria para la comercialización de hongos comestibles en el cantón bucay proyectado al 2009 - Muñiz Chique, Jackson (2009)
This is investment project that is based on the creation, commercialization in of eatable mushrooms in the Bucay Canton, as our country Ecuador continues with an economic instability reflected in the unemployment rates, inflation and migration show that are raised for these last year; due to the bad administration of the post governments. Fact that worry; but motivate to the directors of this article to contribute with the socioeconomic progress of the country. To help to the poor people of the agricultural sector; emerges the idea to create a community microenterprise for the production and commercialization of a novel agricultural product. There will product shiitake mushrooms due to its nutritional and medicinal properties, which help to improve the nutrition in the human being. The place where this mushroom will be produced mush have a mild climate, choosing so, to the Bucay canton (Guayas province). In this canton will be improved the quality of life of a poor agricultural community. Bucay has a community of 15 families settled down in the enclosed area. El Limon, whom want to help. There will form an anonymous society with these farmers, who will be the owners and workers. In addition, they will contribute with capital and/or personal thing and labor. The thing that stands out, which every family owns a plot of land. The commercialization of the product will be in Guayaquil, where the commercial movement is active be supermarkets, municipal markets, hotels and restaurants